1978
DOI: 10.1121/1.381852
|View full text |Cite
|
Sign up to set email alerts
|

Acoustical properties of the human skull

Abstract: The acoustical properties insertion loss, reflection loss, and sound speed were measured on a series of fresh and subsequently formalin immersed human skulls. Measurements were made in the frequency range from 0.25 to 6 MHz. Most studies were restricted to an upper frequency limit of 2.2 MHz. An axisymmetric focused beam configuration was used as the sound source for the measurements and the receivers were small disk-type (3-mm-diam) piezoelectric ceramics. The geometric and temporal character of the focused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
402
1
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 544 publications
(429 citation statements)
references
References 0 publications
24
402
1
2
Order By: Relevance
“…The speed of sound in the outer table was from 2940 to 2960 m/s. The range for the speed of sound in the entire temporal bone was also reported to be from 2570 to 3030 m/s by Fry and Barger (1978). Goldman and Hueter (1955) and Goss et al (1978) reported a speed of sound in skull of 3360 m/s at 0.8 MHz.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The speed of sound in the outer table was from 2940 to 2960 m/s. The range for the speed of sound in the entire temporal bone was also reported to be from 2570 to 3030 m/s by Fry and Barger (1978). Goldman and Hueter (1955) and Goss et al (1978) reported a speed of sound in skull of 3360 m/s at 0.8 MHz.…”
Section: Discussionmentioning
confidence: 97%
“…Intracranial -3 dB beam widths were very similar to those in the free field at all three frequencies. Beam dimensions of a 0.5-MHz transducer were quantified intracranially by Fry and Barger (1978), who similarly noted negligible reduction in the -6 dB beam width (not more than 0.4 mm). Fry and Barger (1978) determined the attenuation coefficients of a single human temporal bone both experimentally and numerically for a range of frequencies from 0.25 to 2.00 MHz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other locations in the body, the SNR from the brain can be particularly poor given the significant attenuation of US by the skull (Fry and Barger 1978). As SNR decreases, the variance in the pulse amplitude estimate increases.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of TPI over TCD for assessing CVR is the use of tissue rather than blood as the signal source. US backscatter from tissue is significantly stronger than that from blood which is particularly important when imaging the brain given the significant attenuation of US by the skull (Fry and Barger 1978). Because of this, TCD is generally limited to imaging blood flow in the major cerebral blood vessels that supply large portions of the brain.…”
Section: Discussionmentioning
confidence: 99%